2007
DOI: 10.1128/jcm.02085-06
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation-Independent Analysis of Changes in Bacterial Vaginosis Flora Following Metronidazole Treatment

Abstract: PCR was used to survey bacterial vaginosis flora before and after metronidazole treatment. The species composition for pretreatment patients was variable. Lactobacillus iners was prominent in all patients posttreatment. Atopobium vaginae concentrations were highest for patients who failed or responded incompletely to treatment and lowest for patients who were cured.Bacterial vaginosis (BV) is the most common cause of vaginal irritation and is associated with adverse pregnancy outcomes (4, 13) and an increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
71
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 21 publications
7
71
0
Order By: Relevance
“…The remaining communities found in 27% of the women formed a large heterogeneous group (IV) and were typified by higher proportions of strictly anaerobic bacteria, including Prevotella, Dialister, Atopobium, Gardnerella, Megasphaera, Peptoniphilus, Sneathia, Eggerthella, Aerococcus, Finegoldia, and Mobiluncus. This finding is consistent with those of previous studies wherein the species composition of vaginal communities was investigated by cloning and sequencing of 16S rRNA genes (17)(18)(19)(20)(21)(22)(23)(24). It should be pointed out that although communities of group IV seem to be diverse relative to the other groups ( Fig.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The remaining communities found in 27% of the women formed a large heterogeneous group (IV) and were typified by higher proportions of strictly anaerobic bacteria, including Prevotella, Dialister, Atopobium, Gardnerella, Megasphaera, Peptoniphilus, Sneathia, Eggerthella, Aerococcus, Finegoldia, and Mobiluncus. This finding is consistent with those of previous studies wherein the species composition of vaginal communities was investigated by cloning and sequencing of 16S rRNA genes (17)(18)(19)(20)(21)(22)(23)(24). It should be pointed out that although communities of group IV seem to be diverse relative to the other groups ( Fig.…”
Section: Resultssupporting
confidence: 82%
“…These species are thought to play key protective roles by lowering the environmental pH through lactic acid production (12,13), by producing various bacteriostatic and bacteriocidal compounds, or through competitive exclusion (13)(14)(15)(16). The advent of culture-independent molecular approaches based on the cloning and sequencing of 16S rRNA genes has furthered our understanding of the vaginal microbiota by identifying taxa that had not been cultured (17)(18)(19)(20)(21)(22)(23)(24). However, this technique is limited by high cost and low throughput, hence only small numbers of samples have usually been analyzed, and the depth of sample analysis was not great.…”
mentioning
confidence: 99%
“…were not the dominant species in 27% of the women who were surveyed (30). This was an intriguing result because the participants did not report any vaginal symptoms (including malodor and discharge) on direct questioning despite having a microbial community that was similar in composition to that of women diagnosed with clinically defined BV (28,81). Interestingly, Klebanoff et al demonstrated in a larger study of 2,888 women that as many as 50% of women with high Nugent scores (indicative of BV) are asymptomatic (24).…”
Section: Bacterial Diversity Of the Human Vaginamentioning
confidence: 80%
“…Today, most studies apply culture-independent techniques to evaluate microbial communities such as the vaginal microbiota (Antonio et al, 1999;Heilig et al, 2002). These techniques are based on the analysis of DNA without relying on cultivation of the bacteria and can yield valuable information about the complexity of the microbial community (Byun et al, 2004;Bradshaw et al, 2006b;Ferris et al, 2007).…”
Section: Introductionmentioning
confidence: 99%